2015
DOI: 10.2807/1560-7917.es2015.20.20.21135
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of West Nile virus in Europe: knowledge gaps and research priorities

Abstract: West Nile virus (WNV) is continuously spreading across Europe, and other continents, i.e. North and South America and many other regions of the world. Despite the overall sporadic nature of outbreaks with cases of West Nile neuroinvasive disease (WNND) in Europe, the spillover events have increased and the virus has been introduced into new areas. The high genetic diversity of the virus, with remarkable phenotypic variation, and its endemic circulation in several countries, require an intensification of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
168
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 110 publications
3
168
0
10
Order By: Relevance
“…pipiens populations that are dominated by biotype pipiens play an important role in the natural transmission cycle of WNV in birds, whereas the risk of WNV outbreaks among humans is increased in populations with high levels of hybridization [8]. Up to now, outbreaks of WNV among humans have only occurred in southern and central Europe, including Italy [34]. The overall proportion of hybrids is higher in The Netherlands than Italy, which is not consistent with the more equal proportion of biotypes in Italy than in The Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens populations that are dominated by biotype pipiens play an important role in the natural transmission cycle of WNV in birds, whereas the risk of WNV outbreaks among humans is increased in populations with high levels of hybridization [8]. Up to now, outbreaks of WNV among humans have only occurred in southern and central Europe, including Italy [34]. The overall proportion of hybrids is higher in The Netherlands than Italy, which is not consistent with the more equal proportion of biotypes in Italy than in The Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of mosquitoes developing resistance against insecticides should not be neglected. Furthermore, a recent study identified knowledge gaps concerning vector control in Europe and urged that the most appropriate and environmental friendly control strategies should be identified, given the reduced availability of products for mosquito control in recent years [54]. …”
Section: Discussionmentioning
confidence: 99%
“…The intensified surveillance for WNV infections in humans and animals resulted in the detection and isolation of many pathogenic isolates of WNV, classified in at least seven different lineages [2,3]. However, two major WNV lineages, lineage 1 (L1) and lineage 2 (L2), are responsible for the outbreaks observed in the past years.…”
Section: Wnv Virology and Clinical Perspectivementioning
confidence: 99%